2018
DOI: 10.1002/vnl.21633
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle size of fly ash (FA) on the interfacial interaction and performance of PVC/FA composites

Abstract: In this study, the effect of particle size of fly ash (FA) on the interfacial interaction between the filler particles and the polymer matrix is investigated. Structural and physical characterization of FA with different particle sizes show that its chemical composition is highly dependent on the particle size. The mechanical, dynamicmechanical, structural, and microstructural properties of the composites are evaluated. Interfacial interaction between FA particles and the polymer matrix is assessed experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…It can therefore be concluded that the mechanical properties of particulate plastic-based composites depend significantly on the particle size of the inorganic fillers, considering the facts that the chemical compositions of three types of CA are similar, and the particle sizes of CA are smaller than that of the slag aggregate. The experimental findings comply with the literature that the mechanical properties improve as the particle size of fillers decreases in inorganic particle-reinforced polymeric composites [ 11 , 34 ]. Parvaiz et al [ 35 ] also concluded that the smaller particle-sized fillers substantially increased the specific area of the filler, which could effectively improve the load transfer between polymer matrix and reinforcing fillers.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It can therefore be concluded that the mechanical properties of particulate plastic-based composites depend significantly on the particle size of the inorganic fillers, considering the facts that the chemical compositions of three types of CA are similar, and the particle sizes of CA are smaller than that of the slag aggregate. The experimental findings comply with the literature that the mechanical properties improve as the particle size of fillers decreases in inorganic particle-reinforced polymeric composites [ 11 , 34 ]. Parvaiz et al [ 35 ] also concluded that the smaller particle-sized fillers substantially increased the specific area of the filler, which could effectively improve the load transfer between polymer matrix and reinforcing fillers.…”
Section: Resultssupporting
confidence: 89%
“…Yao et al [ 7 ] used circulating fluidized bed combustion fly ashes as a filler after they were coated by stearic acid in polymer composites to increase the toughness of the composites. In addition, Khoshnoud and Abu-Zahra [ 11 ] experimentally studied the effect of the particle size of fly ash on the mechanical properties of Polyvinyl chloride (PVC) matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Different types of fillers or aggregates like clay and fly ash were used with polymer to overcome these problems. [11,12] Results showed that fly ash has the ability to act as pozzolonic material that may react for a long and prolonged period to strengthen the composites. [11] The addition of a second or co-polymer to a cement or clay mix can significantly enhance the properties of the resulting material.…”
Section: Introductionmentioning
confidence: 99%
“…The native composite had a tensile strength of 45.4 MPa and this increased to a value of 61.6 MPa for 30% filler of 300 mesh size and later strength reduced to a value of 52.3 MPa for 50% filler of the same size. The surface area is higher for smaller particles size; therefore better interfacial adhesion and load transfer between filler and polymer thus improved mechanical properties [24]. At higher filler concentration tensile strength decreased this was probably because of agglomeration of OPA additives thus causing premature failure [25].…”
Section: Mechanical Properties Of Micro Compositesmentioning
confidence: 99%